The Role of Policy Implementation in Connecting International Labor Standards and Poverty Reduction among Migrant Workers - Inka Nusamuda Pratama; Ajai Saputra; Izmy Ratih Azizah (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study examines the implementation of International Labor Standards (ILS) at the local level within the context of integrating international labor law instruments into poverty alleviation strategies for former migrant workers and other vulnerable groups in Indonesia. It highlights how international normative instruments, including the ILO Constitution and the Declaration of Philadelphia, function not only as legal frameworks but also as discursive tools that shape policy agendas and government responses. Using a qualitative approach, this study employs a Systematic Literature Review (SLR) of scientific publications published between 2015 and 2025, sourced from the Dimensions and Scopus databases. The inclusion criteria consisted of full-text journal articles in English or Indonesian that addressed local poverty alleviation and labor-related issues. The findings reveal that effective implementation of ILS depends on the harmonization of national regulations with international standards and the capacity of labor inspectorates to enforce labor protections. Evidence from regions such as Central Lombok underscores the importance of intersectoral collaboration and evidence-based policymaking to support the reintegration of former migrant workers into decent employment. The study also highlights the gap between normative commitments and policy implementation at the local level.